Cardiovascular Disease Outcomes Related to Early Stage Renal Impairment After Liver Transplantation. Issue 7 (July 2018) - VanWagner, Lisa B.; Montag, Samantha; Zhao, Lihui; Allen, Norrina B.; Lloyd-Jones, Donald M.; Das, Arighno; Skaro, Anton I.; Hohmann, Samuel; Friedewald, John J.; Levitsky, Josh
Abstract : Background: In the general population, even mild renal disease is associated with increased cardiovascular (CV) complications. Whether this is true in liver transplant recipients (LTR) is unknown. Methods: This was a retrospective cohort study of 671 LTR (2002-2012) from a large urban tertiary care center and 37 322 LTR using Vizient hospitalization data linked to the United Network for Organ Sharing. The 4-variable Modification of Diet in Renal Disease equation estimated glomerular filtration rate (eGFR). Outcomes were 1-year CV complications (death/hospitalization from myocardial infarction, heart failure, atrial fibrillation, cardiac arrest, pulmonary embolism, or stroke) and mortality. Latent mixture modeling identified trajectories in eGFR in the first liver transplantation (LT) year in the 671 patients. Results: Mean (SD) eGFR was 72.1 (45.7) mL/min per 1.73 m 2 . Six distinct eGFR trajectories were identified in the local cohort (n = 671): qualitatively normal-slow decrease (4% of cohort), normal-rapid decrease (4%), mild-stable (18%), mild-slow decrease (35%), moderate-stable (30%), and severe-stable (9%). In multivariable analyses adjusted for confounders and baseline eGFR, the greatest odds of 1-year CV complications were in the normal-rapid decrease group (odds ratio, 10.6; 95% confidence interval, 3.0-36.9). Among the national cohort, each 5-unit lower eGFR at LT was associated with a 2% and 5% higher hazard of all-cause and CV-mortality, respectively ( P < 0.0001), independent of multiple confounders. Conclusions: Even mild renal disease at the time of LT is a risk factor for posttransplant all-cause and CV mortality. More rapid declines in eGFR soon after LT correlate with risk of adverse CV outcomes, highlighting the need to study whether early renal preservation interventions also reduce CV complications. Abstract : The authors identify renal impairment as a predictor of both all-cause and cardiovascular mortality after liver transplantation. Supplemental digital content is available in the text.